“Riskology of teaching” as a new interdisciplinary scientific field of risk study in the designing of the teaching process - Ζαγκότας, Βασίλειος; Φύκαρης, Ιωάννης (Επιστημονική Επετηρίδα Παιδαγωγικού Τμήματος Νηπιαγωγών Πανεπιστημίου Ιωαννίνων, 2020)
The process of teaching design, within which teaching is prepared before its classroom application, includes the account of a number of factors that influence the effectiveness of teaching. The teacher within the access of various scientific fields can draw information on each factor separately. In this way, the analysis of "risk in teaching" is a distinct interdisciplinary process. This paper’s suggestion is the development of a new scientific field related to “risk analysis in teaching”, by introducing the term “Riskology of Teaching”. On this basis, the paper attempts to provide a substantiated presentation of this new scientific field’s specific theoretical basis as well as its applications. The basic aims is both to develop a more effective teaching design procedure and to apply a successful teaching process as well.